An end-to-end instrument model for the proposed E-ELT instrument METIS - Schmalzl, E; Meisner, J; Venema, L; Kendrew, S; Brandl, B; Blommaert, J; Glasse, A; Lenzen, R; Meyer, M; Molster, F; Pantin, E (2012)
The optimal performance of an instrument relies critically on accurate performance estimates during its design phase. They need to be modeled to give the science and engineering teams a preview of the performance of the instrument, to guide the design process, to prove the capabilities of the instrument and to prepare science ready software tools before the instrument is operational. METIS, the Mid-infrared E-ELT Imager, is an instrument concept for the E-ELT that covers the thermal infrared wavelengths from 2.9-14μm (L, M and N band). It contains a diffraction limited imager and an integral field high resolution spectrograph. The instrument consists of two independent units, the imager and the spectrograph, and is entirely encased in a cryostat to maintain the stable low temperatures required for good performance at mid-infrared wavelengths. METIS was identified in the instrument roadmap as the third instrument for the E-ELT, after two first light instruments. Because in the mid-infrared the Earth's atmosphere and the telescope mirrors radiate and produce a very high thermal background, it is crucial to develop techniques and mechanisms to measure and reduce this background, to achieve the desired performance of an E-ELT. To demonstrate the capabilities of METIS, years before the actual instrument is built and can be tested, we are developing an end-to-end instrument model, which will simulate the full capacity of METIS. The structure of the model and first results of the performance evaluation are shown. © 2012 SPIE.